The Roots of Chinese Cultural Psychology that China Cope With COVID-19 Disease - Bing-quan, Li; Hai-xin, Du (Advances in Social Sciences Research Journal, 2020)
Chinese successful campaign against the COVID-19 disease has its roots of Chinese cultural psychology. The characteristics of Chinese cultural psychology, such as unremitting self-improvement, social commitment, people-oriented thoughts, collectivism, positive attribution and self-reflection, responsibility and dedication, etc, have provided spiritual support and inexhaustible power for China to overcome this disease. It is the reasons that we should further enhance our cultural confidence, vigorously carry forward and develop China’s fine traditional culture, and actively carry out Chinese cultural psychological education.